Evaluating sources of baseline data using dual‐criteria and conservative dual‐criteria methods: A quantitative analysis. Issue 4 (26th April 2020) - Falligant, John Michael; McNulty, Molly K.; Kranak, Michael P.; Hausman, Nicole L.; Rooker, Griffin W.
Abstract : Scheithauer et al. (2020) recently demonstrated that differences in the source of baseline data extracted from a functional analysis (FA) may not affect subsequent clinical decision‐making in comparison to a standard baseline. These outcomes warrant additional quantitative examination, as correspondence of visual analysis has sometimes been reported to be unreliable. In the current study, we quantified the occurrence of false positives within a dataset of FA and baseline data using the dual‐criteria (DC) and conservative dual‐criteria (CDC) methods. Results of this quantitative analysis suggest that false positives were more likely when using FA data (rather than original baseline data) as the initial treatment baseline. However, both sources of baseline data may have acceptably low levels of false positives for practical use. Overall, the findings provide preliminary quantitative support for the conclusion that determinations of effective treatment may be easily obtained using different sources of baseline data.